Independence as aim and condition: Discursive consequences of how institutional residence for people with intellectual disability in Sweden was problematized in 1985’s policy on institutional dismantling. (Sociologisk Forskning, 2025)
Despite Sweden often being described as having undergone a comprehensive deinstitutionalization process with an accompanied national dismantling of large institutions, there are indications that repressive elements remain present in support services for people with intellectual disabilities (ID). This article focuses on this discrepancy by using a methodological adaptation of Bacchi's WPR-tool to analyze how institutions were problematized in connection to 1985’s policy on institutional dismantling. The analysis shows that institutional residence for people with ID was consistently problematized based on its segregation and size. From this problematization, independence emerges as a significant discourse, both understood as the aim of community housing for people with ID and as the value that conditions whether or not housing is regarded as a “real home”. The article concludes by discussing the contingency of the problematization of institutional residence in relation to the lack of problematization of the institutions’ repressive elements, something that is argued as linked to the persistence of repressive structures in contemporary support services.
Keywords: deinstitutionalization; intellectual disability; Bacchi; independence; policy; restrictive measures